2017
DOI: 10.1016/j.tranon.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Positive Expression of Programmed Death Ligand 1 in Peritumoral Liver Tissue is Associated with Poor Survival after Curative Resection of Hepatocellular Carcinoma

Abstract: BACKGROUND: Recurrence or metastasis of hepatocellular carcinoma (HCC) is mainly intrahepatic after curative resection, demonstrating that the peritumoral environment is important but often neglected. Programmed death ligand 1 (PD-L1) in intratumoral liver tissues is a poor prognosis factor whose impact is removed after curative resection. However, PD-L1 expression remains in the peritumoral liver tissues and its distribution and prognostic value are still not clear. METHODS: We assessed the expression of PD-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…The presence of PD-L1-positive monocytes in the peritumoral stroma was shown to be an independent prognostic factor of overall survival (OS) in hepatocellular carcinoma (HCC) [20]. Another study of HCC reported that the peritumoral PD-L1 expression in hepatocytes is an independent prognostic factor for survival [21]. Therefore, the expression of checkpoint biomarkers in peritumoral tissue as part of the tumor microenvironment should also be investigated to determine their potential role in the tumor immune escape mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of PD-L1-positive monocytes in the peritumoral stroma was shown to be an independent prognostic factor of overall survival (OS) in hepatocellular carcinoma (HCC) [20]. Another study of HCC reported that the peritumoral PD-L1 expression in hepatocytes is an independent prognostic factor for survival [21]. Therefore, the expression of checkpoint biomarkers in peritumoral tissue as part of the tumor microenvironment should also be investigated to determine their potential role in the tumor immune escape mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…PD‐L1 expression in peritumoral hepatocytes is also an independent prognostic factor for OS and disease‐free survival (DFS). Dai et al suggested that future anticancer therapy should target not only residual tumor cells but also the “soil” promoting tumor growth. The levels of circulating PD‐L1 might also be of prognostic value in patients with HCC.…”
Section: Pd‐l1 Predicts Poor Prognosis In Patients With Hccmentioning
confidence: 99%
“…PD-L1 overexpression may reflect the presence of endogenous host immune response to tumor and serve as a biomarker for predicting survival benefits from adjuvant CIK cell immunotherapy in HCC patients ( 16 ). And peritumoral PD-L1 expression was associated with significantly worse survival compared to the negative expression group ( 17 ). However, the results of some studies are reversed.…”
Section: Introductionmentioning
confidence: 97%